Proceedings of SPE/DOE Improved Oil Recovery Symposium 2002
DOI: 10.2523/75178-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cost Reduction and Injectivity Improvements for CO2 Foams for Mobility Control

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper identifies chemical cost reduction derived from the synergistic effects of co-surfactant systems using a good foaming agent and a less expensive poor foaming agent. The required good foaming agent is reduced by at least 75%. Also the effect on injectivity is reduced by as much as 50% using the co-surfactant system, compared to a previously used surfactant system. Mobility control of injected CO 2 for improved oil recovery can be achieved with signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…5 Earlier studies using lignosulfonate as a sacrificial agent or a cosurfactant demonstrated a significant reduction in the expensive surfactant adsorption. [6][7][8][9][10][11][12][13][14][15][16] Lignosulfonates (also called lignin sulfonates and sulfite lignins) are derived from the reaction of wood lignin with bisulfite or sulfate ions during the wood digestion reaction to make pulp. 17 Lignin, said to be the most common polymer on Earth, 17 is derived from abundant renewable resources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Earlier studies using lignosulfonate as a sacrificial agent or a cosurfactant demonstrated a significant reduction in the expensive surfactant adsorption. [6][7][8][9][10][11][12][13][14][15][16] Lignosulfonates (also called lignin sulfonates and sulfite lignins) are derived from the reaction of wood lignin with bisulfite or sulfate ions during the wood digestion reaction to make pulp. 17 Lignin, said to be the most common polymer on Earth, 17 is derived from abundant renewable resources.…”
Section: Introductionmentioning
confidence: 99%
“…Grigg and Tsau demonstrated that lignosulfonate could reduce the adsorption of the primary foaming agent-CD1045 TM by 24-60% in Berea core and 15-29% in Indiana limestone core samples. [12][13][14][15][16] In an earlier study the effect of concentration, salinity, temperature and injection rate on the equilibrium adsorption density and the effect of postflush rate, brine concentration and composition, temperature on the calcium lignosulfonate (CLS) desorption process in Berea sandstone cores were performed. 19 Equilibrium and kinetics are basic to the proper understanding of adsorption and desorption processes between surfactants and rocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] However, costs incurred by the loss of expensive foaming chemicals to adsorption on reservoir rocks often exclude this potentially beneficial option for many reservoirs. 8,9 Published IOR work on surfactant adsorption has focused on studying adsorption equilibrium with little mention of kinetics. [10][11][12] However, the kinetics of surfactant adsorption are important in determining the rate of adsorption onto the rock and the time required to reach equilibrium, and are thus useful in predicting the transport and fate of surfactant in the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effects of pressure on IFT observed that trends also depended on the system studied. [60][61][62][63][67][68][69][70][71] Experiments were conducted on aqueous CD and a dense CO 2 system at different CD concentrations (Table 3). The pressure at which experiments were conducted ranged from 800 psig to 2000 psig at constant temperature of 25ºC (77ºF).…”
Section: Temperature Effect On Interfacial Tensionmentioning
confidence: 99%